CSK: uma abordagem para estruturação de kernel de tempo real em componentes - Correia, Lúcio José Herculano (2004)
Generally, operating systems offer a set of services through primitives that are used on demand by applications. Similarly, software components implement and provide services through well-defined interfaces, which are reused in different software projects of a problem domain. Based upon this similarity, it is researched the reuse of software components in real time operating systems projects. It is presented CSK (Computer Structured Kernel) approach for structuring a real time kernel with software components. The approach is divided in two phases. In the first one software components are built from the legacy code and documentation of a preexisting kernel. In the second one, that kernel is rebuilt by reusing the produced components. A case study applies CSK to real time kernel Virtuoso.